Hydrogen production via CO2 dry reforming of glycerol over ReâNi/CaO catalysts - Mohd Arif, N.N. (Elsevier Ltd, 2018)
The present work investigates the performance of Re-promoted Nickel-based catalyst supported on calcium oxide for glycerol dry reforming reaction. The catalysts were prepared using wet impregnation method and their catalytic performance was tested in a packed bed reactor with CO2 to glycerol ratio (CGR) of 1â5, reaction temperature of 600â900 Â°C and gas hourly specific velocity (GHSV) of 1.44 Ã 104â7.20 Ã 104 ml gcat â1 sâ1. The optimum operating temperature for both Ni/CaO and ReâNi/CaO is 800 Â°C, with the GHSV of 3.6 Ã 104 mL gcat â1sâ1. The optimum CGR for Ni/CaO and ReâNi/CaO is 1.0 and 3.0, respectively. At this condition, hydrogen gas is directly produced from glycerol decomposition and indirectly from water-gas-shift reaction. After 2 h at the optimum conditions, 5 ReâNi/CaO gives optimal glycerol conversion and hydrogen yield of approximately 61 and 56, respectively, while in comparison to 15 Ni/CaO, the conversion and yield are 35 and 30, respectively. Characterization of the spent catalysts showed the existence of whisker carbon from the CO2 hydrogenation and methanation processes. By comparing to 15 Ni/CaO, the addition of Re increases the acidic sites of the catalyst and enhanced the surface adsorption of OH group of the glycerol. The adsorbed glycerol on the catalyst surface would further react with the adsorbed CO2 to yield gases products. Thus, the catalytic activity improved significantly. Â© 2018 Hydrogen Energy Publications LLC